Mechanism of Ginkgo biloba Extract in the Treatment of Tinnitus Based on Network Pharmacology - Huang, Qiao; Hou, Tao; Ren, Yi; Liao, Xingwei; Du, Kejiang; Yin, Shihua (Letters in Drug Design & Discovery, 2024)
ObjectiveThis study aimed to examine the active constituents and therapeutic targets of Ginkgo biloba extract (GBE) through a network pharmacology methodology to elucidate the mechanisms underlying the efficacy of GBE in treating tinnitus.MethodsThe active constituents and potential targets of GBE were identified via the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database, while tinnitus-related targets were sourced from the GeneCards database. Protein-protein interaction (PPI) data relevant to tinnitus were retrieved from the STRING database. Subsequently, an active constituent-target network was constructed, and Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were conducted using Cytoscape 3.7.1.ResultsThe analysis identified 27 active constituents and 73 potential therapeutic targets of GBE relevant to tinnitus treatment. A total of 418 GO terms were identified, including 408 biological processes, 4 cellular components, and 6 molecular functions, which were associated with processes, such as cell cycle regulation, apoptosis, inflammatory response, oxidative stress, and angiogenesis. Additionally, 116 KEGG pathways were identified, including pathways involved in cancer, the AGE-RAGE signaling pathway in diabetic complications, human cytomegalovirus infection, and apoptosis, among others.ConclusionThe treatment of tinnitus with GBE may target several potential therapeutic candidates, including MYC, TNF, AKT1, CXCL8, CASP3, IL6, TP53, VEGFA, PTGS2, EGFR, EGF, JUN, ESR1, MMP9, CCND1, and MAPK1. This approach may involve various mechanisms, such as anti-inflammatory, antioxidant, and anti-apoptotic pathways. Network pharmacology provides a robust framework for further investigation into the pharmacological targets and molecular mechanisms through which GBE may exert its effects in the context of tinnitus.
Keywords: targets